(4+5+6+7+8+9)-(9+8+7+6+5+4)-3-2-1=22+2-30=-6
4 5 6 7 8 9 9 8 7 6 5 4 3 2 1=22 2 30添上﹙﹚﹛﹜[]﹣﹢÷×-+…………等符号
1个回答
相关问题
-
1+1×2+2×3+3×4+4÷5+5÷6+6÷7+7÷8+8÷9+9÷10+10=?
-
添符号1( )2( )3( )4( )5( )6( )7( )8( )9=10
-
6-2 3 5 = 18 9 13 ÷9= 5.6× 4 7 = 1 3 + 1 6 = 8÷ 4 7 = 4 5 ÷0
-
30÷6= 72÷8= 27÷3= 42÷7÷3= 18÷9= 8×2= 5×9= 56÷8×5= 4×7= 36-6=
-
6/7×5/9+4/9×6/7(简便计算) 0.8-(2/3+1/12)×8/9 5/6÷(6-5/12-7/12
-
3×(-9)+7×(-9) (5/4-7/6)×(-8/7) (-54)÷6÷(-3) (-54)÷6÷(-3) 2×{
-
3.6÷0.4-1.2×5 90÷【3.6-1.8】 【31.6-11.7】÷2.5÷0.4 3.4×7.8÷3.9 5
-
6÷1/4=18×5/6=3/4×3/5=4/9÷8/9=7/6×3/14=
-
1/2÷4/5÷(2/9×3/8) (5/6-3/4)÷5/12÷9/5 3/7÷[5/7-(3/7+1/5)] 简便计
-
能简便得要简便:(4/7+8/9)×2/25 (5/6-5/9)×18/5 1÷(1-3/4×8/9÷5/6) 19/2